A travessia transatlântica de recordações e os atravessamentos em Souvenirs: uma análise descritiva da tradução de um romance de Lima Barreto - Amaral, Regina Almeida do (2024)
Considering that the Brazilian reception and critique of the inaugural novel of Lima Barreto (1881-1922) published in 1909, Recordações do Escrivão Isaías Caminha, influenced the national construction of the author’s image and his work as a whole, this work proposes a descriptive analysis of Souvenirs d’un gratte-papier, the French translation of this novel — translated by Monique Le Moing and Marie-Pierre Mazéas and published in 1989 — with the aim of identifying in this translated text which discourse about Lima Barreto and his works is disseminated (is it a mere reproduction of what was disseminated in Brazil or is there the creation of new discourses and complementary or substitute images?) and checking whether it influenced the elaboration of the target-text. It starts from a polysystemic perspective, based on Even-Zohar’s Polysystem Theory (1990) and its developments by Gideon Toury (2012), a theoretical framework that allows us to look at the translated text both as a target-culture fact (Toury, 2012, p. 18), a result of relationships with systems internal to that culture, and as a result of relationships with source-culture systems (Even-Zohar, 1990), intra- and intersystemic relationships, seen here as intersections that affect a text that goes through the crossing of a translation. For this purpose, the target-text analysis will be divided into two parts: the first, dedicated to identifying the discourse present in the paratexts of the translated text, and the second, focus on the translated text itself that, it is hoped, will allow seeing the discourse behind maintenances, transformations, and erasures. The methodology of this work is based on the scheme proposed by Lambert and Van Gorp (2011), enriched with contributions from Torres (2011), who is dedicated to observing the paratexts and accompanying discourse in works of Brazilian literature translated into French, and from Berman (1995), with his sketch of a method and notions of translator’s position, translation project and translator’s horizon.